SCREENING FOR THE TOTAL PHENOLIC CONTENT OF SELECTED MANGROVE SPECIES COLLECTED FROM SUNDARBAN MANGROVE FOREST - SAUROV SETT; SOUMYA KUNDU; ABHIJIT MITRA; ANINDITA BANERJEE; ARUP KUMAR MITRA (International Journal of Pharma and Bio Sciences, 2014)
In this present research, acetone extracts of Avicennia alba and Aegialitis rotundifolia were investigated for the estimation of their total phenolic content. The amount of total phenol present was calculated by assaying it with Folin’s Ciocalteau Reagent and spectrophotometric analysis. Gallic acid was taken as the standard compound and the total phenolic content of each of the plant sample was expressed as mg/g Gallic acid equivalent (GAE). The standard curve equation was found out to be y=0.0597x+0.0198; R2 = 0.9536. The results showed that A. rotundifolia had higher total phenolic content (53.23 mg/g GAE) than that of A. alba (42.147 mg/g GAE).Since antioxidant property and total phenol content are directly related, these plant leaf extracts could be used for various medicinal and agroeconomic development.